Hillsville Remembered : Public Memory, Historical Silence, and Appalachia's Most Notorious Shoot-Out - Rountree, Travis A. (The University Press of Kentucky, 2023)
Hillsville Remembered: Public Memory, Historical Silence, and Appalachia's Most Notorious Shoot-Out is the first book-length scholarly review of the Hillsville Massacre. This comprehensive study examines a variety of sources written about and inspired by the event and casts light on how the incident helped reinforce the nation's conception of the region through depictions of this sensational moment in history. Author Travis A. Rountree uses rhetorical analyses to trace and reflect on the texts and contexts surrounding the events that have been reported, preserved, interpreted, and reinterpreted with different voices in various formats. In all, this book provides an extensive analysis of the Hillsville Massacre and reveals new understandings of the production of memories and stories that evolved from the event.